Collective action problems: Disentangling possible feedback loops between government policies and the public's value-change - Eivind Hoff-Elimari; Anat Bardi; Simon Matti; Kristina Os̈tman (European Journal of Government and Economics (EJGE), 2014)
Solving collective action problems, such as poverty reduction or climate change, depends on interactions between governments' and voters' preferences regarding pro-social actions. This paper examines whether the overall direction of change in pro-social public policy precedes public value-change, rather than the other way around. We examine change in the public's pro-social values in six European countries, as measured by the European Social Survey (ESS) during 2002-2012. In these countries, we conducted an expert survey to rate governmental policy that expresses these values over the same period, thereby examining value-change in governmental policy. The chronological comparison of value-change of the public with that of respective governments suggests that changes in pro-social government policies may drive public value-change rather than vice versa. This complements previous studies focused on the opinion-policy connection. Possible political implications are discussed. The promising findings of this initial study point to the importance of conducting larger-scale future studies.
Keywords: 330; Values; policy feedback; democracy